Síntese e avaliação in vitro do potencial antimicrobiano, antiproliferativo e tripanocida de derivados sulfonamídicos do eugenol e diidroeugenol - Barbosa, Helloana Azevedo (2017)
Bioactive natural products are potential sources for the treatment of various diseases associated with high mortality rates in the world population, such as cancers and infectious diseases. Some phenylpropanoids, especially eugenol, which are present in the essential oils of several plant species, demonstrate relevant activities as antimicrobials and antiparasitics. In addition, there are several scientific reports that demonstrate the antiproliferative potential of eugenol against distinct lines of tumor cells. Likewise, several substances containing the sulfonamide functional group have been cited as responsible for important biological effects such as antibacterial, antifungal, antiparasitic and anticancer. In order to obtain new bioactive products and in view of the biological actions related to the use of eugenol and sulfonamides, it was proposed herein the use of molecular hybridization strategy in the design of new substances that contained structural motifs of eugenol or dihydroeugenol and a sulfonamide subunit. The eight final proposed substances were successfully obtained from the condensation of p-acetamidobenzenesulfonyl chloride with ortho and meta-aminophenols derivatives, which came from nitrated derivatives of eugenol or dihydroeugenol. The products checked by infrared spectroscopy, nuclear magnetic resonance and mass spectroscopy. They were evaluated as antimicrobials against Gram-positive (Staphylococcus aureus, Bacillus cereus and Enterococcus faecalis) and Gram-negative bacteria (Escherichia coli, Pseudomonas aeruginosa and Salmonella typhimurium) and against pathogenic or opportunistic species of Candida (C. albicans, C. tropicalis, C. krusei, C. glabrata and C. parapsilosis). Anti-Trypanosoma cruzi activity in epimastigote forms of the parasite and antiproliferative activity against cell lines derived from human cancers (A549, HepG2, HT144 and MCF7) were also evaluated. Three sulfonamides derivatives (7a, 7b and 7c) presented antibacterial activity with IC50 values ranging from 299.40 to 297.62 μM, against Bacillus cereus and Staphylococcus aureus. Six sulfonamides derivatives (6a, 6c, 7a, 7b, 7c and 7d) exhibited antifungal activity with IC50 values between 664.89 and 748.50 μM, against C. albicans, C. krusei, C. glabrata and C. parapsilosis. In the evaluation of trypanocidal activity, all eight sulfonamides derivatives were active with IC50 values in the range of 217.26 to 420.21 μM. In the evaluation of antiproliferative activity, only three derivatives (6b, 6d and 7a) exhibited promising activity against the breast adenocarcinoma line (MCF7) with IC50 values between 116.60 and 164.90 μM. Even though the IC50 values found in these biological assays are higher than those obtained for the reference drugs, it is important to note that in some cases the proposed hybrid substances have resulted in less toxic and more active products than their phenylpropanoid precursors. Therefore, they represent new molecules that can be altered structurally for optimization of activity.